Effect of an Incremental Interval Endurance Rope-Training Program on Antioxidant Biomarkers and Oxidative Stress in Non-Active Women - Bahloul Ghorbanian; karim Azali alamdari; Yousef Saberi; Fariba Shokrolahi; Hakime Mohamadi (Kurdistan University of Medical Sciences, 2018)
Background & Aim: Aerobic exercises are recommended as an important technique to control and prevent cardiovascular diseases and metabolic disorders. Therefore, this study aimed to evaluate the effect of an incremental interval endurance rope-training program on antioxidant biomarkers and oxidative stress in non-active women. Materials & Methods: This quasi-experimental research was conducted on non-active female subjects (overweight and obese) at the age range of 20-30 years. In total, 20 eligible participants were selected via random sampling and divided into two control and intervention groups of 10. The training program included eight weeks (four 45-minute sessions per week) of incremental rope training. Data analysis was performed in SPSS version 20 using dependent and independent t-tests at the significance level of 0.05. Results: The results of dependent t-test showed a significant increase in the level of superoxide dismutase enzyme, total antioxidant capacity, and glutathione peroxidase, compared to the pre-test state of the subjects (P<0.05). Meanwhile, a significant decrease was detected in the level of malondialdehyde (P>0.05). Moreover, results of independent t-test demonstrated a non-significant increase in the total antioxidant capacity and glutathione peroxidase in subjects of the intervention group, compared to the control group. On the other hand, there was a significant increase and decrease in superoxide dismutase and malondialdehyde, respectively (P<0.05). Conclusion: According to the results of the study, rope training increased antioxidant defense and decreased oxidative damage and lipid peroxidation. Therefore, it seems that this type of training can prevent cardiovascular diseases in overweight and obese individuals.